The Effect of Digital Literature, Entrepreneurship Literature, and Entrepreneurship Behavior on Marketing Performance of Traditional Market Traders in Dinoyo Malang (Case Study of Traders on Malang Online Platform) - Septia Anggi Saputri; Agung Winarno; Wening Patmi Rahayu (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to determine whether there is a direct and indirect influence between Digital Literacy, Entrepreneurial Literacy on Marketing Performance, and Entrepreneurial Behavior in the Dinoyo traditional market. This study uses a discrete/normal quantitative approach, that is, this data is obtained from the calculation results of traders who join the online platform application. The sampling technique was 200 respondents. Data analysis of this research was carried out using the Statistical Package for the Social Sciences (SPSS) method using SPSS. The results of this study are that: 1) Digital Literacy has a positive and significant direct effect on Marketing Performance with a Beta value of 0.367 and Entrepreneurial Behavior with a Beta value of 0.269 2) Entrepreneurial Literacy has a positive and significant direct effect on Marketing Performance with a Beta value of 0.238 and Entrepreneurial Behavior with a Beta value of 0.364. 3) Entrepreneurial Behavior has a positive and significant with a Beta value of 0.221 direct effect on Marketing Performance 4) Digital Literacy has a positive and significant with a Beta value of 0.350 direct effect on Marketing Performance through Entrepreneurial Behavior 5) Entrepreneurial Literacy has a positive and significant with a Beta value of 0.318 direct effect on Marketing Performance through Entrepreneurial Behavior. Based on the results of this study, the researchers suggest that this research is not only one product, so that it can be generalized widely. Because at this time digital cannot be separated from aspects of human life along with the times. Understanding of digital literacy, entrepreneurial literacy, and entrepreneurial behaviour can improve the marketing performance of traders. Keywords Employee Digital Literacy, Entrepreneurship Literacy, Entrepreneurial Behavior, Marketing Performance.